Biofuel scale-up from waste source and strategies for cost optimization - Shalyda, Md Shaarani; Aizi Nor Mazila, Ramli; Nor Hasmaliana, Abdul Manas; Rabiatul Adawiyah, Ahmad; Siti Fatimah Zaharah, Mohd Fuzi; Zatul Iffah, Mohd Arshad (Elsevier, 2023)
The search for alternate fuels that demonstrate alleviated environmental impact is intensifying globally. To measurably displace fossil fuels in the near future, several aspects should be considered when promoting biofuel technology. Renewable sources, especially wastes from biomass, are feasible to be converted into biofuels of different phases (gaseous, liquid, and solid). This chapter discusses the thermochemical and biological biomass conversion routes, along with the essential processes involved to produce biofuels. The advantages and limitations of each approach are being compared. Significant operating parameters that require optimization for process scale-up are identified and reviewed. The strategies for cost optimization are also outlined in the final part of this chapter.